THE INFLUENCE OF SERVICE QUALITY ON COMMUNITY SATISFACTION AT THE BATUMANDI PUBLIC HEALTH CENTER (UPT PUSKESMAS) IN BALANGAN DISTRICT - Mawarti Mawarti; M. Ridha Anshari; M. Noor Fuadi (PT. Antis International Publisher, 2024)
Objective: This study aims to assess the influence of service quality on community satisfaction at the Batumandi Public Health Center (UPT Puskesmas) in Balangan Regency, Indonesia. It also investigates the factors that affect community satisfaction. Method: The research uses a quantitative descriptive approach, collecting data through questionnaires, observations, and documentation. A total of 96 patients from the 2,267 people who visited in 2021 were sampled using the Slovin formula. The data were analyzed using SPSS 25 for validity, reliability tests, and regression analysis. Results: The study found that service quality dimensions—Tangible, Reliability, Responsiveness, Assurance, and Empathy—affected community satisfaction. Among these, Tangibles and Reliability showed the highest satisfaction rates. The regression analysis revealed a strong correlation (R = 0.949) and confirmed that service quality significantly impacts community satisfaction, with a determination coefficient of 90%. Factors like inadequate facilities and insufficient socialization of the online registration system were identified as key influencers. Novelty: This research provides valuable insights into the service quality factors at a rural health facility and offers practical recommendations for improving healthcare services in Indonesia’s community health centers